Moral Development Strategy through the Santri Program at the Roudlotul Jannah Student Islamic Boarding School (PPM) Surakarta - Latif Hanif Mustofa; Dartim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to determine strategies for developing student morals, as well as supporting and inhibiting factors through several moral development programs for students at the Roudlotul Jannah Student Islamic Boarding School (PPM) Surakarta. This research is qualitative research with field research methods, as well as data collection techniques through interviews, observation and documentation. Sources of research data were obtained from ustadz, boarding school caregivers, and santri. After the data is collected, data analysis techniques are carried out including data reduction, data presentation, and drawing conclusions. The research results show that the main strategy for developing santri morals at PPM Roudlotul Jannah Surakarta is through example, habituation, advice and punishment. Some of the superior programs implemented in developing the morals of santri include congregational prayers, cults, grand cleaning, evening roll call, basic Fridays, daily infaq, and santri bonding evenings. The role of the ustadz as a role model and a conducive Islamic boarding school environment are supporting factors for the moral development of students. Meanwhile, excessive use of gadgets and student academic pressure are factors that hinder the moral development of students. This research concludes that the moral development of students at PPM Roudlotul Jannah Surakarta is quite effective through the implementation of relevant strategies and programs, although there are still several obstacles that must be overcome.